Kitty Foyle [videorecording (DVD)] - Wood, Sam, 1883-1949; Hempstead, David; Trumbo, Dalton, 1905-1976; Rogers, Ginger, 1911-1995; Morgan, Dennis, 1908-1994; Craig, James, 1912-1985; Cianelli, Eduardo, 1887-1969; Cossart, Ernest, 1876-1951; Cooper, Gladys, 1888-1971; Stevens, K. T., 1919-1994; Morley, Christopher, 1890-1957 (Warner Bros. Home Entertainment : distributed by Warner Home Video, 2013)
Kitty, a working-class girl, endures the rejection of Philadelphia society, makes her own way as a single woman, and ultimately chooses between an unmarried arrangement with Main Line scion Wynnewood Strafford VI or marriage to a struggling physician.